The Role of Bank Management in the EU Resolution Regime for NPLs. Issue 2 (5th August 2020) - Kokkinis, Andreas; Miglionico, Andrea
ABSTRACT: During the global financial crisis, the growth of non-performing loans (NPLs) was partly a consequence of lack of regulatory oversight and poor bank internal processes. NPLs require intrusive monitoring tools and effective corporate governance is crucial in dealing with the deterioration of loans; however, perverse incentives to delay their recognition leave the process at risk. The EU legislation has adopted a set of regulatory measures to resolve and restructure non-performing exposures. While existing literature approaches NPLs from a regulatory and accounting perspective, this article takes a distinctive corporate governance view in order to conceptualize the NPL problem. The strategies through which senior management and shareholder incentives may undermine regulatory objectives on NPL disclosure are identified and an evidence-based approach to reconsidering and settling these problems is advanced.